(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Static balance is one of the fundamental motor components that plays an important role in supporting students’ movement efficiency, coordination, and participation in physical activities. However, preliminary observations at SMP Negeri 5 Banjarbaru indicated that many Phase D students experienced difficulties in maintaining body stability during physical education activities, reflecting low static balance ability. Therefore, innovative and engaging learning strategies are needed to enhance students’ balance performance. This study aimed to determine the effectiveness of rope bridge games in improving the static balance ability of Phase D students. This research employed a quantitative approach using a Pre-Experimental method with a One Group Pretest–Posttest Design. The sample consisted of 27 students from class VII B of SMP Negeri 5 Banjarbaru selected through purposive sampling. Static balance ability was measured using the Stork Balance Stand Test. The intervention was implemented through rope bridge game activities integrated into physical education learning sessions. Data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test with a significance level of 0.05. The findings revealed a substantial improvement in students’ static balance ability following the intervention. The mean pretest score increased from 8.22 seconds to 22.38 seconds in the posttest. Furthermore, the Wilcoxon test produced an Asymp. Sig. (2-tailed) value of 0.000, which was lower than 0.05, indicating a statistically significant difference between pretest and posttest results. These findings demonstrate that rope bridge games effectively stimulate postural control, body coordination, and balance maintenance. In conclusion, rope bridge games are an effective and enjoyable learning medium for improving the static balance ability of Phase D students and can be recommended as an innovative strategy in physical education learning.